Examining driving stability and traffic capacity: A simulation study on appropriate speed limits in expressway work zones - Qingwen Guo; Baohua Guo; Ziyan Zhao (PLoS ONE, 2025)
In order to obtain proper speed limits in expressway work zones, CarSim and TruckSim software were used to determine the critical car and truck safe speeds and then VISSIM software was used to determine the traffic capacities and their corresponding speed limits under different upstream transition area lengths and road adhesion coefficients. The results show that critical car and truck safe speeds increase exponentially while traffic capacity and its corresponding speed limit increase logarithmically with rising road adhesion coefficient under a constant upstream transition area length, and critical car and truck safe speeds increase as a power function while traffic capacity and its corresponding speed limit increase exponentially with rising upstream transition area length under a constant road adhesion coefficient. Because Road Traffic Signs and Markings- Part 4: Work Zone (RTSM, GB 5768.4–2017) only gave the relationship between speed limit and upstream transition area length without considering road adhesion coefficient, the obtained determination method of optimal speed limit in expressway work zone in this paper has better reference value.